Disruptions in higher education: Mitigating issues of access and success in the COVID-19 pandemic - Maringe, F.; Chiramba, O. (South African Journal of Higher Education, 2022)
Disruptions create both new opportunities and challenges in higher education. In settled times, education systems plod along with an assumed and uncritical acceptance of normalcy of the status-quo. When the status quo is disrupted, suddenly the patched-up cracks reveal the depth and magnitude of the simmering problems of the sector in graphic ways. Access and success are arguably the two most poignant indicators of the performance of higher education systems. In post-colonial societies such as South Africa, access is used to estimate progress in broadening participation in higher education, particularly to young people from previously disadvantaged communities. Access has two broad meanings: increased enrolments and enhanced epistemological impact. Success, on the other hand is measured variously but mainly through graduation and progression rates across different socio-economic higher education students groups and also on the quality of their performances. In this article we provide a theoretical discussion of the notions of disruptions and their impact in higher education; examine the questions of access and success in higher education; and conclude that the chasm lying between access by participation and access by success requires substantial transformation of a knowledge system that is alien to the cultural context of the country; rebalancing and recalibrating the broader ideological environment that privileges liberalism while paying token attention to social justice and inclusion beyond mere symbolism; and a persistent refocusing on emancipatory pedagogies, designed to liberate rather than subjugate graduates into pigeon holed choices in the labour market which are designed to serve the needs of owners of capital as the primary motive of employment. We conclude by identifying critical factors that appear to lead to a failure by universities to bridge the gap between access by participation and access by success or epistemological access. Most of these tend to be structurally embedded in the fabric of higher education institutions and the sector and include, a persistent coloniality of the sector, disjuncture between the intended ideological framework guiding national development and the operating economic models and institutional inertia to move beyond the canonical bases of higher education based on western epistemes.